Consequences of exchanging the NAP-encoding genes fis and dps in Salmonella enterica Serovar Typhimurium - BOGUE, MARINA MARY (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2020)
The genes encoding nucleoid associated proteins (NAPs) are syntenic among γ-Proteobacteria, and several factors are known to impact gene expression at a given locus, including changes in gene dosage caused by DNA replication. This study sought to investigate the impact of gene dosage, and the contribution of cis-acting regulatory sequences on the expression of two NAP-encoding genes, fis and dps in Salmonella entierica serovar Typhimurium. Further, this study sought to examine the global impact on gene expression by these two factors. Fis and Dps differ in function and are associated with two distinct phases of the growth cycle. Strains were constructed in which the fis and dps open reading frames (ORFs), and in which fis, dps and their cis-acting regulatory regions were exchanged reciprocally with regard to their genome location. The changes in gene dosage and expression patterns of fis and dps were investigated. It was demonstrated that the exchange of fis and dps ORFs has a greater impact on global transcription patterns, and in global Fis binding patterns. Further, exchanging fis and dps ORFs had a greater impact on bacterial physiology. These results indicate that the expression of a gene of interest can be fine-tuned by altering its location in the genome, with regard to its distance from the origin of replication and altering its cis-acting regulatory sequences.
APPROVED
Keywords: Bacterial physiology; Nucleoid associated proteins; γ-Proteobacteria